2001
DOI: 10.1097/00008571-200110000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The human pregnane X receptor: genomic structure and identification and functional characterization of natural allelic variants

Abstract: The pregnane X receptor (PXR)/steroid and xenobiotic receptor (SXR) transcriptionally activates cytochrome P4503A4 (CYP3A4) when ligand activated by endobiotics and xenobiotics. We cloned the human PXR gene and analysed the sequence in DNAs of individuals whose CYP3A phenotype was known. The PXR gene spans 35 kb, contains nine exons, and mapped to chromosome 13q11-13. Thirty-eight single nucleotide polymorphisms (SNPs) were identified including six SNPs in the coding region. Three of the coding SNPs are non-sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
226
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(245 citation statements)
references
References 33 publications
12
226
3
Order By: Relevance
“…Although they were reported to be functional in previous studies, none of the NR1I2 SNPs were found to be correlated with CsA concentrations in our study [5,6,8] . However, most of these studies were in vitro, without the consideration of many possible influences caused by other factors in vivo.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Although they were reported to be functional in previous studies, none of the NR1I2 SNPs were found to be correlated with CsA concentrations in our study [5,6,8] . However, most of these studies were in vitro, without the consideration of many possible influences caused by other factors in vivo.…”
Section: Discussioncontrasting
confidence: 96%
“…The NFKB1 -94ins/del ATTG polymorphism was detected by TaqMan ® SNP Genotyping Assay. Polymorphisms of NR1I2, including T25385C, A24622T, C24446A, G24113A, C4356T, A601G, G7635A, A11156C, and C6994T, were genotyped by direct sequencing [5][6][7][8] .…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…The pregnane X receptor (PXR, encoded by NR1I2) is reported to be the key nuclear receptor regulating the expression of CYP3A4, CYP3A5, and ABCB1 [29] . Several PXR SNPs have been reported to be associated with the CYP3A4 or P-gp/MDR1 expression level or activity in vitro [29][30][31] . Differences in the distribution of PXR SNPs were found when comparing the Han Chinese of South China and Caucasian Americans [31] .…”
Section: Tacrolimusmentioning
confidence: 99%
“…Hence, knowledge with regard to known PXR polymorphisms, which influence the expression of MDR1 and/or CYP3A4, is therefore relevant to understand the interindividual responses towards drugs. [3][4][5] One of the putative relevant polymorphisms is PXR A11156C, because it has been shown that the presence of the 11156C allele is associated with a decreased expression of MDR1-mRNA in intestinal villi cells derived from gut biopsies. 4 In order to determine the genotype of the PXR A11156C polymorphism, we developed a real-time PCR fluorescence resonance energy transfer (FRET) assay.…”
Section: Introductionmentioning
confidence: 99%